The life project as a basic competition in the integral training of middle education students - Díaz-Garay, Iris del Socorro; Narváez-Escorcia, Iris Teolinda; Amaya-De Armas, Tulio (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The objective of this work was to analyze the influence of educational elements in the construction of the life project in middle school students. A mixed approach was used, as variables, qualitative and quantitative were analyzed. The sample consisted of 98 members from four classes (44 students, 24 parents, 25 teachers and 5 teaching directors), from a Colombian public school. The information was collected using techniques and instruments such as participant observation, unstructured interviews, focus groups and a Liker-type questionnaire. The results show little clarity among the participants about the elements, the structure and the way of developing a life project, which teachers and parents provide support and elementary awareness processes that favor its construction and development, but with little guidance from the Institutional support team, unfavorable sociocultural contexts and limited self-assessment and determination of the student to achieve it. It is concluded that it is necessary to implement actions that facilitate agreements between members of the community, that lead young people to start assertive processes of construction of their life projects.